Waste disposal impact from street lighting - Manzano, Eduardo Roberto (2004)
The street lighting management even under an efficient and organised scheme produces waste materials which should be reduced and controlled. In an organised and responsible society this means the necessity to study policies for an adequate reduction of the environmental impact by means of controlled waste disposal or recycling processes for reuse. This paper describes the subject of waste produced by street lighting installations, specially by lamp containing mercury and the possible processing policies.